Determining disease severity - Emel Bülbül Başkan (Galenos Publishing House, 2022)
Assessment of the severity of psoriasis is versatile, and unfortunately, there is no single tool that can assess the severity of this disease in every aspect. As well as psoriasis area and severity index, other tools such as physician's global assessment and body surface area are also used in assessing the severity of psoriasis. The index used to assess quality of life is the dermatology life quality index. This section discusses the methods used in determining the severity of psoriasis, descriptions of treatment phases and goals, and measurement of treatment success.